Detecting Opportunistic Special Items - Cain, Carol Anilowski; Kolev, Kalin S.; McVay, Sarah (Management Science, 2020)
The frequency of special items has increased dramatically over time, offering a convenient conduit for the inappropriate classification of past, present, and future recurring expenses as nonrecurring. Identifying this misclassification is especially important in light of the pervasive use of non–generally accepted accounting principles earnings in recent periods because special items offer camouflage for excluded recurring expenses. Building on prior research, we propose a method for identifying the predicted level of special items, attributing any excess to opportunism, and demonstrate the importance of this partitioning for financial-statement users. In particular, we provide evidence that the opportunistic portion of special items is associated with lower future earnings, cash flows, and returns. We conclude that this portion of special items is more likely to contain opportunistically misclassified recurring expenses that should have been recognized as such in prior, current, or future periods. Thus, we provide a meaningful partition of special items that should be useful to investors, analysts, creditors, auditors, and regulators because each of these parties must assess the implications of special items. This paper was accepted by Suraj Srinivasan, accounting.